Frontispiece: Stereoselective Arene‐Forming Aldol Condensation: Catalyst‐Controlled Synthesis of Axially Chiral Compounds. Issue 53 (21st September 2017) - Witzig, Reto M.; Lotter, Dominik; Fäseke, Vincent C.; Sparr, Christof
Abstract : Stereoselective arene‐forming aldol condensation reactions were investigated which lead to the formation of configurationally stable binaphthalenes, axially chiral amides and oligo‐1, 2‐naphthylenes. This versatile strategy provides various rotationally restricted compounds with high enantioselectivity and is thus expected to be useful in many areas. For more details, see the Concepts article by C. Sparr et al. onpage 12960 ff.